What Does a Systems Approach to Quality Improvement Look Like in Practice? - Sharon Williams (International Journal of Environmental Research and Public Health, 2022)
Universally improving healthcare systems is difficult to achieve in practice with organisations implementing a range of quality improvement (QI) approaches, in varying and changing contexts, and efforts ranging from project-based improvements to whole system change. This study aimed to identify how organisations overcome the challenges to improving the quality of the services they deliver. Drawing on the eight challenges from the ‘Quality and Safety in Europe by Research (QUASER) hospital guide, we assessed eight cases reported by the UK-based regulator Care Quality Commission as improving their performance. A thematic analysis of these secondary data established that all eight challenges had been addressed or considered in varying degrees. Education and physical and technological challenges seemed less prominent than developments made to address other challenges such as developing leadership, structure, and culture to support improving quality. This paper relies on the analysis of secondary case data and one framework to assess improvement efforts. Further research is required to consider other models and frameworks and to collate longitudinal data to capture the dynamics and increasing the maturity of improving healthcare systems in practice.